Antioxidants and Free Radical Scavenging Activity of Brown Algae of Visakhapatnam Coast - Rajagopal, S.V.; Raman, B.V.; Bhaskar Reddy, I.; Rama Rao, M.; Sivakumar, K. (Asian Journal of Chemistry, 2010)
Antioxidant, free radical scavenging activity, total phenolics, total carotenoids, vitamin C and vitamin E content of Padina tetrastomatica, Sargassum illicifolium and Sargassum vulgare were carried out in order to expand their utilization in pharmaceutical and food industry. Fractions rich in phenolics were extracted from three brown algal species using methanol as solvent. Free radical scavenging activity was studied using DPPH photometric assay. Padina tetrastomatica exhibited higher levels of radical scavenging activity, total carotenoids, total phenolics and high vitamin C contents. Whereas, Sargassum species contain high content of vitamin E and low content of phenolics, carotenoids and vitamin C.